(untitled) (Communications in Computational Physics, 2020)
In order to model the dispersal of volcanic particles in the atmosphere and their deposition on the ground, one has to simulate an advection-diffusion-sedimentation process on a large spatial area. Here we compare a Lattice Boltzmann and a Cellular Automata approach. Our results show that for high Peclet regimes, the cellular automata model produce results that are as accurate as the lattice Boltzmann model and is computationally more effective.